2020
DOI: 10.1111/jfpp.15018
|View full text |Cite
|
Sign up to set email alerts
|

Application of chitosan‐based apple peel polyphenols edible coating on the preservation of strawberry ( Fragaria ananassa cv Hongyan) fruit

Abstract: This study was determined to investigate the efficacy of chitosan (CS)‐based apple peel polyphenols (APP) composite coatings to enhance the storage quality of strawberries. Strawberries were coated with CS‐APP1 (0.25% APP), CS‐APP2 (0.50%), CS‐APP3 (0.75%), CS‐APP4 (1.0%), and stored at 20°C and 35–40% RH. The uncoated fruit was considered as control. The fruits were evaluated for weight loss, decay, firmness, bioactive compounds, titratable acidity, and total soluble solids (TSS). The results revealed that CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
51
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(61 citation statements)
references
References 53 publications
9
51
0
1
Order By: Relevance
“…Increased concentration of beeswax increased the hydrophobicity of coatings, which conversely reduced the moisture removal, and consequently, the weight loss from the fruits. This reduction of weight loss in polysaccharide coatings may be associated to better crosslinking between hydroxyl group of polysaccharide and hydrophilic substance (such as phenols) in coatings through hydrogen bonding [33]. The results are supported by the findings of Nasrin et al [34], who used beeswax coatings in combination with coconut oil and observed the similar behavior of weight loss in lemons.…”
Section: Weight Losssupporting
confidence: 68%
“…Increased concentration of beeswax increased the hydrophobicity of coatings, which conversely reduced the moisture removal, and consequently, the weight loss from the fruits. This reduction of weight loss in polysaccharide coatings may be associated to better crosslinking between hydroxyl group of polysaccharide and hydrophilic substance (such as phenols) in coatings through hydrogen bonding [33]. The results are supported by the findings of Nasrin et al [34], who used beeswax coatings in combination with coconut oil and observed the similar behavior of weight loss in lemons.…”
Section: Weight Losssupporting
confidence: 68%
“…According to the antioxidant activity by the DPPH method (Figure 5), the coated and uncoated fruits present significant differences, as well as the days evaluated (p < 0.05), where the coated fruits have higher antioxidant activity, similar results found for blackberry (Rubus glaucus Benth) for ten days [23], raspberry (Rubus spp) for eight days [36], raspberry (Rubus ulmifolius subsp sanctus) for nine days [37], and strawberry (Fragaria ananassa cv Hongyan) for six days [38].…”
Section: Discussionsupporting
confidence: 59%
“…CS-based coatings enriched with olive (olive leaves and pomace), apple (peel) or pomegranate (peel) extracts, in strawberry and guava fruits maintain higher levels of AA than the uncoated samples, decreasing during storage [ 47 , 82 , 83 ]. Furthermore, montmorillonite (MMT) has been incorporated as nano-fillers into CS coatings, with different percentage, to investigate their effects on storage of tangerines and table grapes [ 84 , 85 ].…”
Section: Reactive Oxygen Species and Antioxidant Systemsmentioning
confidence: 99%
“…In CS-coated litchi, sweet cherry, blueberry, strawberry, longan, and pomegranate fruits have been detected a lower reduction of anthocyanin content compared to uncoated ones probably due to their enzymatic degradation owing to anthocyanase, PPO, and peroxidase (POD) throughout the storage period [ 11 , 45 , 49 , 64 , 66 , 67 , 70 , 78 , 83 , 92 , 97 , 104 , 114 ].…”
Section: Reactive Oxygen Species and Antioxidant Systemsmentioning
confidence: 99%